Prehistoric fisherfolk of Oman: the Neolithic village of Ras Al-Hamra RH-5 - Marcucci, Lapo Gianni; Badel, Émilie; Genchi, Francesco (The Archaeological Heritage of Oman, 2021)
Prehistoric Fisherfolk of Oman' reports on excavations at the prehistoric site Ras Al-Hamra RH-5, located on a large promontory in the Qurum area of Muscat, conducted by the Italian Archaeological Mission in Oman with support from the Ministry of Heritage and Tourism. The site dates from the late fifth to the end of the fourth millennia BC and comprises an accumulation of superimposed food discards deriving from continuous and repeated subsistence activities such as fishing, collecting shells, hunting and herding. Dwellings and household installations, including objects of daily use and ornaments, have also been found throughout the occupation sequence. Excavations at RH-5 yielded unprecedented data on the economic and social dynamics of Neolithic societies in eastern Arabia. The exploitation of different ecological niches supplied all the necessary requirements for year-round sedentary human occupation. The lifestyle of fisher-gatherer communities during the Middle Holocene represents a fundamental step of the neolithisation process in Oman
Keywords: Archéologie -- Oman

The Early Iron Age Metal Hoard from the Al Khawd Area (sultan Qaboos University) Sultanate of Oman - Jawhari, Nasser Said al-; Yule, Paul A.; Douglas, Khaled; Pracejus, Bernhard; Belushi, Mohammed Ali K. al-; ElMahi, Ali Tigani (The Archaeological Heritage of Oman, 2021)
Numerous metallic artefacts, which anciently were deposited in a hoard, came to light per chance on the campus of the Sultan Qaboos University in Al Khawd, Sultanate of Oman. Mostly fashioned from copper, these arrowheads, axes/adzes, bangles, daggers, knives, socketed lance/ spearheads, metal vessels, razors, rings, swords, and tweezers compare well with numerous documented artefact classes from south-eastern Arabia assigned to the Early Iron Age (1200-300 BCE). Discussion of the international trade between ancient Makan, Dilmun, and Mesopotamia during the 3rd millennium BCE dominates the archaeological literature about Arabia archaeology. The Al Khawd hoard and its contemporaries lend weight to the suggestion that 1st millennium BCE Qadē (the name of south-eastern Arabia at that time) was even more important than Bronze Age Makan in terms of the copper trade volume. A reassessment shows the Early Iron Age by no means to be a dark age, but rather an innovative, successful adaptive period characterised by evident population growth
Keywords: Archéologie -- Oman

Rock Art Scenes from Wadi Fida, Oman - El-Mahi, Ali Tigani (أدوماتو, 2021)
Keywords: Archéologie -- Oman

The skeletal remains from Umm an-Nar tomb QA 1-1: spatial distribution and anthropological analysis - Rutkowski, Łukasz; Parol, Marta (Polish Archaeology in the Mediterranean, 2021)
Collective aboveground circular tombs of stone are one of the main categories of architectural structures from the Umm an-Nar period (2500–2000 BC) in the Oman peninsula. The tombs have been known since the late 1950s but various aspects of their functioning still await a full explanation. Most of them survived in poor condition, often empty, only a dozen or so actually yielding any human remains. Tomb QA 1-1, one of ten Umm an-Nar-type tombs at Wadi al-Fajj in northwestern Oman, has yielded a substantial assemblage of human skeletal remains (estimated MNI 25) from the two of four burial chambers excavated between 2016 and 2018. While the excavation of the tomb should be continued, a presentation of the bone assemblage recovered to date, including a distribution analysis of the remains, deposition characteristic, and preliminary osteological analysis, adds to the existing source base of Early Bronze Age populations in the ancient land of Magan.
Keywords: Archéologie -- Oman

Husn al-Baleed, a mediaeval fortified castle along the Omani coast: preliminary results from the 2016-2017 excavations - Pavan, Alexia (Contacts between South Arabia and the horn of Africa, from the Bronze age to Islam: in honor of Rémy Audouin, 2021)
Keywords: Archéologie -- Oman

Archaeobotanical analysis of food and fuel procurement from Fulayj fort (Oman, 5th-8th c. CE) including the earliest secure evidence for sorghum in Eastern Arabia - Dabrowski, Vladimir; Bouchaud, Charlène; Tengberg, Margareta; Zazzo, Antoine; Priestman, Seth (Journal of Arid Environments, 2021)
Keywords: Archéologie -- Oman